2019
DOI: 10.1177/0269215519889394
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Internet-based self-management program for cancer-related fatigue patients: a systematic review and meta-analysis

Abstract: Objective: To systematically investigate how fatigue, depression, anxiety, sleep quality, and life quality are influenced by the Internet-based self-management program (IBSMP) among cancer patients. Data sources: Eight databases (Cochrane Library, Ovid, Web of Science, Medline, Embase, Chinese biomedical database (CBM), China National Knowledge Infrastructure (CNKI), and Wanfang) were systematically searched from inception to January 2019. Methods: The aim of this study is to identify randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…• • Chronic obstructive pulmonary disease, 62 improving quality of life, reducing hospital admissions, but possibly increasing mortality; 63 • • Stroke, improving quality of life; 64 • • Fatigue in people with fatigue associated with cancer and its treatment. 65,66 The common components of successful community-based programmes 67 are also mostly achieved through education about: In summary, there is good evidence that practicing functional activities and undertaking cardiorespiratory exercise are both important interventions in any rehabilitation service. Education is also an important intervention, although its content is less well established; it probably always includes knowledge about the disease; its causes, prognosis, and treatments; and teaching skills in relation to self-management.…”
Section: Education and Self-managementmentioning
confidence: 99%
“…• • Chronic obstructive pulmonary disease, 62 improving quality of life, reducing hospital admissions, but possibly increasing mortality; 63 • • Stroke, improving quality of life; 64 • • Fatigue in people with fatigue associated with cancer and its treatment. 65,66 The common components of successful community-based programmes 67 are also mostly achieved through education about: In summary, there is good evidence that practicing functional activities and undertaking cardiorespiratory exercise are both important interventions in any rehabilitation service. Education is also an important intervention, although its content is less well established; it probably always includes knowledge about the disease; its causes, prognosis, and treatments; and teaching skills in relation to self-management.…”
Section: Education and Self-managementmentioning
confidence: 99%
“…A recent review found that internet-based programs are effective in reducing LTSE. 30 Maybe physiotherapist should be more aware of advising patients to seek information online in combination with their treatment. However, it is important to recommend specific homepages, otherwise patient's lack trust in information from the Internet.…”
Section: Comparison With Previous Studies and Theoriesmentioning
confidence: 99%
“…Learning symptom self‐management (SM), a process through which a patient engages in learned health behaviors and daily management of their illness, 6 can decrease symptom severity and improve quality of life 7,8 . As households are increasingly connected to the Internet, 9,10 many online education materials are available to support cancer patients in learning how to self‐manage symptoms 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Learning symptom self‐management (SM), a process through which a patient engages in learned health behaviors and daily management of their illness, 6 can decrease symptom severity and improve quality of life 7,8 . As households are increasingly connected to the Internet, 9,10 many online education materials are available to support cancer patients in learning how to self‐manage symptoms 7 . Online resources are accessible to a larger population, including those who might otherwise not have direct access to a healthcare professional (HCP), 7,9 who prefer to address such issues independently rather than attending face‐to‐face support groups or workshops to learn these skills, 11 or whose medical care is being shifted to a telemedicine format in the context of the COVID‐19 pandemic 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation